2021
DOI: 10.1080/2162402x.2021.1988403
|View full text |Cite
|
Sign up to set email alerts
|

Local tumor microbial signatures and response to checkpoint blockade in non-small cell lung cancer

Abstract: In cancer patients, the clinical response to checkpoint-based immunotherapy is associated with the composition and functional quality of the host microbiome. While the relevance of the gut microbiome for checkpoint immunotherapy outcome has been addressed intensively, data on the role of the local tumor microbiome are missing. Here, we set out to molecularly characterize the local non-small cell lung cancer microbiome using 16S rRNA gene amplicon sequencing of bronchoscopic tumor biopsies from patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…(1) Tumor microbiome (TM): Although the correlation of the GM and CI outcomes has been well studied, data on the role of the local TM, an important part of the tumor microenvironment, are insufficient. Some studies have explored the correlation between the TM and CI and found the TM can also promote oncogenesis ( 94 ) and affect the treatment effect ( 95 ). The interaction of the TM and the GM influenced the host immune response and tumor growth ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Tumor microbiome (TM): Although the correlation of the GM and CI outcomes has been well studied, data on the role of the local TM, an important part of the tumor microenvironment, are insufficient. Some studies have explored the correlation between the TM and CI and found the TM can also promote oncogenesis ( 94 ) and affect the treatment effect ( 95 ). The interaction of the TM and the GM influenced the host immune response and tumor growth ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, local samples can directly modulate NSCLC development and influence the treatment efficacy. For example, local tumor microbial signatures are markers for immunotherapy response in NSCLC ( 5 ). So far, very limited studies have applied different sample types form LC patients to conduct the comprehensive analysis of LM features.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses revealed the consistent presence of bacterial signatures in the samples and suggested high intratumoral abundance especially of Firmicutes, Bacteroidetes, and Proteobacteria. 43 Interestingly, a higher microbial tumor diversity was associated with improved overall survival irrespective of ICI treatment response, indicating treatmentunrelated beneficial effects of tumor microbial diversity in NSCLC patients. 43 Our analyses further showed that high tumorous abundance of Gammaproteobacteria was associated with low PD-L1 expression and poor progressionfree survival (PFS), suggesting that Gammaproteobacteria are preferentially found in PD-L1 low-expressing tumors which typically do not respond well to ICI therapy.…”
Section: Clinical Relevance Of the Tumor-associated Microbiomementioning
confidence: 97%
“…88 Tumor-associated and other tissue microbiomes typically entail a low to very low microbial biomass which can only be investigated using highly sensitive and specific methods. 43 50 55 In the absence of prior knowledge allowing for more targeted investigations, researchers typically aim at dissecting the bulk tumor-associated microbiome (or bacteriome), thus making 'universal species coverage' a top priority. All these criteria are met by modern sequencing-based technologies which have therefore prevailed in the systematic profiling of microbes from clinical samples such as tumor tissue.…”
Section: Techniques and Challenges In Profiling The Tumor-associated ...mentioning
confidence: 99%